2017
DOI: 10.3390/polym9120676
|View full text |Cite
|
Sign up to set email alerts
|

A Porous Cobalt (II) Metal–Organic Framework with Highly Efficient Electrocatalytic Activity for the Oxygen Evolution Reaction

Abstract: A 3D porous framework ([Co 1.5 (tib)(dcpna)]·6H 2 O) (1) with a Wei topology has been synthesized by solvothermal reaction of 1,3,5-tris(1-imidazolyl)-benzene (tib), 5-(3 ,5 -dicarboxylphenyl)nicotinic acid (H 3 dcpna) and cobalt nitrate. The electrocatalytic activity for water oxidation of 1 has been investigated in alkaline solution. Compound 1 exhibits good oxygen evolution reaction (OER) activities in alkaline solution, exhibiting 10 mA·cm −2 at η = 360 mV with a Tafel slope of 89 mV·dec −1 . The high OER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 57 publications
1
15
0
1
Order By: Relevance
“…Electrochemical water splitting is considered an efficient way to produce hydrogen through the half-reaction of the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) [9,10,11,12,13,14]. However, the process of electrochemical water splitting is severely plagued by the reaction kinetics of the OER at the cathode [15,16,17,18]. To date, noble metal catalysts based on platinum, ruthenium and iridium are the most efficient catalysts for the OER, but their high cost and scarcity render them impracticable for large scale industrial applications [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical water splitting is considered an efficient way to produce hydrogen through the half-reaction of the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) [9,10,11,12,13,14]. However, the process of electrochemical water splitting is severely plagued by the reaction kinetics of the OER at the cathode [15,16,17,18]. To date, noble metal catalysts based on platinum, ruthenium and iridium are the most efficient catalysts for the OER, but their high cost and scarcity render them impracticable for large scale industrial applications [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was demonstrated to be able to perform 21 TONs with a TOF of 0.035 s –1 under photocatalytic conditions, whereas if supported onto FTO (fluorine-doped tin oxide), ZIF-67 operates under a wide range of pH, requiring 1.73 V vs NHE to give a stable current of 1 mA/cm 2 (at pH 9) . Nevertheless, the performances are quite far from those required for applications, because the poor conductivity of the framework generally hampers the direct use of MOFs in electrocatalysis. Alternatively, MOFs can be subjected to framework degradation either by thermal decomposition, chemical oxidation, or in situ electrochemical aging, , in order to afford carbon/metal or metal oxide composites with improved performances. As an example, An et al demonstrated that thermal decomposition of ZIF-67 affords ultrathin Co 3 O 4 nanomesh, rich in oxygen defects, with remarkable performances at pH 14 (η = 370 mV at 10 mA/cm 2 and a Tafel slope of 74 mV/dec), whereas Wang and co-workers improved the performances of Zn 0.2 Co 0.8 OOH via chemical oxidation of ZIF-67 in the presence of (NH 4 ) 2 S 2 O 8 , lowering η 10 to only 235 mV …”
Section: Introductionmentioning
confidence: 99%
“…The overpotential value of the Co-MOF-5 microfiber catalyst was compared with similar MOF-based electrocatalysts; the related values are tabulated in Table S1 and the corresponding histogram image is given in Figure . Table S1 shows that the OER activity of Co-MOF-5 microfibers was higher than those of other reported catalysts. This outstanding electrochemical performance was mainly attributed to the structural aspects, porosity, and intrinsic nature of the fibrous materials. Owing to their exceptional activity, other transition-metal MOF-based fibrous materials can be utilized in other energy-related applications also in the future.…”
Section: Resultsmentioning
confidence: 99%